Analisis Tipe Rumah Tinggal Terhadap Ancaman Bahaya Tsunami Di Kota Banda Aceh: Studi Kasus: Kecamatan Kuta Alam dan Syiah Kuala - Soviana, Widya; Husaini, Husaini (University of Muhammadiyah Aceh, 2024)
People who lived on the Banda Aceh City shoreline lost their houses in the 2004 tsunami tragedy. The likelihood of a tsunami tragedy in the future might rise if homes are rebuilt in the original location. The goal of this study was to determine the most common building types and the degree of susceptibility of residential structures to the tsunami catastrophe in the districts of Kuta Alam and Syiah Kuala. Through a sample approach, a questionnaire was given out to the community in the districts of Kuta Alam and Syiah Kuala, with a total of 105 responses. To gather representative home building types at the research site, a survey was undertaken. data processing with the use of the validity and reliability tests in SPSS. The questionnaire was deemed legitimate as a result of the validity test, which produced average R count values of 0.1918 and higher than the value of r table. The reliability test findings were dependable since they had a Cronbach Alpha score of 0.671, which is higher than 0.6. The predominant home types in the Kuta Alam and Syiah Kuala subdistricts are type B (good) and type C (poor) dwellings. Low, medium, and high levels of vulnerability were used to determine how vulnerable residential buildings were to the tsunami tragedy in the Kuta Alam District. The Syiah Kuala District, meanwhile, had high and moderate degrees of vulnerability. According to the physical state of the environment in the districts of Kuta Alam and Syiah Kuala, 19% of the coastal regions are still in their original state, and 81% of the territory is made up of grib stones and mangroves. In the Kuta Alam sub-district, there are 11 villages overall, with the percentage of vulnerable structures falling into one of three categories: low (45.45%), medium (45.45%), or high (9.09%). In the Syiah Kuala District, however, the degree of vulnerability of residential structures was determined from a total of 10 villages, and it was divided into two classes: medium, with a percentage of 40%, and high, with a percentage of 60%. As a result, it's important to upgrade the design of communal housing in coastal locations, such as by constructing homes with two or more levels.